Epidemiological Investigation and Endoscopic Findings in Children Under 14 Years of Age with Foreign Body Ingestion Referred to Yazd Shahid Sadoughi Hospital in Yazd City - Roohollah Edalatkhah; Majid Aflatoonian (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2024)
Introduction: Foreign body ingestion is a relatively common and sometimes life-threatening problem. This study was conducted with the aim of investigating the types of foreign body and endoscopic findings in children under 14 years old in Yazd Shahid Sadoughi Hospital in Yazd City. Methods: This descriptive-cross-sectional study was conducted on 50 children under 14 years of age who referred to the Pediatric Emergency Department of Shahid Sadoughi Hospital with foreign body ingestion in 2018. Demographic information, clinical symptoms, type of foreign body, time interval between ingestion and referral, time interval between the time of referral to endoscopy and findings during endoscopy were collected and analyzed with SPSS version 16. Results: The average age of the children was 37.14 ± 39.10 months. Out of the 50 children investigated, 33 (66%) were boys and 17 (34%) were girls. The most common clinical symptom was asymptomatic with a frequency of 42%, the most common foreign body was coin (24%), the most common age range was 1-5 years (48%), the most common lesion in endoscopy was the absence of a lesion (56%) and The most common location of the object in endoscopy was stomach (50%) . No statistically significant difference was found between the frequency distribution of endoscopic findings (type of lesion and location of lesion) according to the variables: age, sex and type of foreign body in the investigated children (p>0.05). Conclusion: The probability of foreign body ingestion is higher in boys and the children aged 1-5 years, so more attention should be paid to these children. Most cases of ingestion of foreign bodies are asymptomatic, but due to serious complications, diagnostic measures should not be postponed.